Concepções de ensino de professores que lecionam matemática nas fases iniciais da educação básica - Silva, Helena Soares da (2013)
This research, linked to the Post-Graduation Program in Education, from the University Campus Rondonópolis, Federal University of Mato Grosso (PPGEDU / CUR / UFMT), the line of Teacher Education and Educational Public Policy aimed to investigate the domain elements of Piaget's theory and its manifestation in the teaching practice of teachers who teach mathematics in the third stage of the first cycle of basic education. The theoretical approach focused on discussions about the epistemological conceptions: empiricism, rationalism and Piaget constructivism . The study is characterized as qualitative investigative nature, and the literature research field constituted the used methodological tools , including the questionnaire and observation as data collection tools. The field research was conducted in a school of municipal schools in Rondonópolis - MT and occurred during the months of March and April 2012, with the observation of three classes of research subjects, teachers of the third phase of the first cycle of education basic, because at this stage of education is still necessary to work with concrete materials. The survey questionnaire was designed and applied in order to capture the concepts that permeate the mathematics education of these teachers, the data collected is complete with classroom observations. The analysis in relation to mathematics education was based on the design of Jean Piaget, which argues that knowledge evolves through the construction and reconstruction, organizing actions through contact with the environment. The teaching of mathematics in thinking of that Epistemologist, implies in studying and applying the structures of intelligence operative finding a suitable method in order to overcome the structural natural methods not reflective. The search for understanding of the best way to build the knowledge depends on many social factors, which involve administrative actions and policies in the school environment and other higher authorities related to them. Thus, the center of discussions of this research turned to theoretical considerations and scientific by this author. The results showed that there is a gap of the pedagogical practices of the teachers surveyed in relation to the proper character of Piaget's genetic epistemology, as well as his theory of construction of mathematical thinking. Conceptions of mathematics teaching,observed in responses and practice of teachers, denote greater importance to the investigation. The study revealed certain weaknesses in teacher education in relation to the construction of knowledge of mathematics in the early stages of the first cycle of basic education and this observation allows us to say that the theories developed by Piaget are relevant to teacher training, since they help in understanding the process of learning mathematics, using concrete objects focused on the accumulated experiences of the educator and the student.